The Effect of Entrepreneurship Education and Social Media on Student’s Entrepreneurial Intention : The Perspective of Theory of Planned Behaviour and Social Media Use Theory - Sutrisno, Sutrisno; Prabowo, Heri; Kurniawan, Bayu (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to investigate the effect of entrepreneurship education and social media use on students’ entrepreneurial interest using the Theory of Planned Behaviour and Social Media Use Theory approaches. This study used a survey method with a quantitative research approach, involving 139 student respondents from Semarang City, Indonesia, through an online questionnaire. The data analysis techniques used were Structural Equation Modeling (SEM) and Partial Least Square (PLS). The results of this study indicated a positive and significant relationship between entrepreneurship education, social media, and students’ entrepreneurial intention. Thus, based on the principles of the Theory of Planned Behaviour and Social Media Use Theory, entrepreneurship education provided understanding, skills, and support to consider self-employment as a career. In contrast, social media provides access to information, social interaction, motivation, role model influence, and norms that support entrepreneurship, creating an ecosystem that supports students’ entrepreneurial intentions.